Comparison and analysis of the biomechanics of the lower limbs of female tennis players of different levels in foot-up serve - Liang, Zhiqiang; Wu, Jinan; Yu, Jiabin; Ying, Shanshan; Liu, Zhiyong; Zhang, Yu; Gu, Yaodong; Li, Jianshe (Frontiers in Physiology, 2023)
Purpose: The purpose of this study was to examine biomechanical performance of the foot-up serve (FUS) in female tennis players at different skill levels. Methods: FUS analysis was completed in the biomechanical laboratory by 32 female college tennis players at three different levels. During FUS, 3D-biomechanical data from tennis players’ lower limbs were collected. One-way ANOVA was used to examine differences in kinematic and kinetic data between groups Results: Range of motion (ROM) of bilateral lower-limb joints revealed significant differences in kinematics performance during both the preparation and landing cushion phases (p < 0.05). During preparation, Level 3 was significantly longer than Level 2 (P-a = 0.042, P-b = 0.001, and P-c = 0.006). During the flight phase, significant differences between levels 1 and 3 (P-a:0.002) and levels 1 and 2 (P-c:0.000) were discovered (P-a:0.002 and P-c:0.000). There were significant height differences between levels 1 and 2 as well as between levels 1 and 3. (P-a = 0.001, P-c = 0.000). During serve preparation (P-c = 0.001) and landing, GRF’s peak was significantly higher than level 3. (P-c:0.007). Significant differences were found between groups in the LLS preparation stage, with level 3 significantly higher than levels 1 and 2. (P-a = 0.000, P-b = 0.001, and P-c = 0.000); during landing, level 2 LLS was significantly higher than levels 1 and 3. (P-a = 0.000, P-b = 0.000, and P-c = 0.035). Conclusion: The range of motion of joints and the stiffness of the lower limbs have a significant impact on a tennis player’s FUS performance. A larger of joint mobility and lower-limb stiffness promote better performance during the FUS preparation stage.